THE EFFECT OF HEAVY METAL ON SEED GERMINATION AND PLANT GROWTH - Ng, Wai Fong (2018)
Heavy metals pollution had become one of the biggest issue happening in this world and is getting worse each day which could bring adverse effects toward organisms such as plants. Cadmium released to environment through anthropogenic activities such as metal extraction & combustion of fossil fuels whereas nickel is released into the air by power plants and trash incinerators. Plants uptake heavy metals such as cadmium and nickel that are present in the environment which affect their growth or eventually die. This study was carried out to determine the effect of heavy metals namely Cadmium (Cd) and Nickel (Ni) on the seed germination and growth of Extreme Yield Red Chili. Firstly, the seeds were grown in Petri dishes containing different concentrations ranging from 0 to 300 mg/L of both cadmium (Cd) and nickel (Ni) solution for 14 days. Negative control is prepared by just adding deionized water. All treatments were prepared in 4 replicates. The length of shoots and roots for each treatment were observed and measured at day 7 and day 14. As shown in the results, 0.1 mg/L and 0.5 mg/L for Ni concentration did not had massive effect on the growth as both of them had a longer roots and shoots formation which is 1.86 cm and 1.37 cm at day 14. Cd shown the similar results which 0.1 mg/L and 0.5 mg/L had the longest length of roots and shoots which is 3.6 cm and 2.7 cm at day 14. The germination percentage was also calculated at day 7 and day 14 and the results showed that Ni had a 100% of seed germination when the concentration was at 1, 50 and 150 mg/L while Cd concentration at 1 mg/L. In conclusion, Ni and Cd were not able to affect the seed germination but could affect the growth of shoots and roots